Pengendalian Persediaan Pallet Packaging untuk Packaging Cigarette Paper dengan Metode Economic Order Quantity (EOQ) di PT BM - Nurhayati, Sinta; Rahma, Rana Ardila; S., Ade Momon (Fakultas Teknik Universitas Tulang Bawang, 2025)
In the cigarette paper industry, pallet packaging plays a crucial role in the supply chain. It helps protect cigarette paper from physical damage and environmental factors during transportation and storage. PT BM faces several challenges, one of which is inefficiency in inventory management, leading to unnecessary costs in production and distribution processes. This study applies the Economic Order Quantity (EOQ) method to determine the optimal order quantity of raw materials, ensuring a smooth production process. The calculation results show that implementing the EOQ method leads to more efficient total inventory costs compared to the company's previous ordering policy. For local pallets, the optimal order quantity changed from 3,600 sets ordered 12 times per year (costing Rp 43,200,000.00) to 514,208 sets ordered only 3 times per year (costing Rp 10,800,000.00). A similar improvement was observed for export pallets, where the order quantity changed from 3,600 sets ordered 24 times per year (costing Rp 52,200,000.00) to 338,327 sets ordered only 3 times per year (costing Rp 6,525,000.00). Additionally, the total inventory cost using the EOQ method was recorded at Rp 38,333,333.33 for local pallets and Rp 36,912,500.00 for export pallets. Keywords: EOQ, Inventory, Pallet Packaging